POTENSI TAMBAK IKAN BANDENG TERHADAP KESEJAHTERAAN MASYARAKAT DI KASAI KECAMATAN PULAU DERAWAN - Syam, Irma (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2026)
The purpose of this research was to identify and analyze the potential of milkfish ponds for community welfare in Kasai, Pulau Derawan District. This research was conducted with three milkfish pond farmers as respondents. Based on the research results, to obtain an in-depth overview of the potential of milkfish ponds and their impact on community welfare in Kasai, Pulau Derawan District, the researcher conducted direct interviews with three pond owners as primary informants.